IMPLEMENTATION OF FUZZY LOGIC USING SUGENO METHOD OF SCHOLARSHIP DETERMINATION - Boy, Boy Alberto Sitanggang (Yayasan Kita Menulis, 2022)
Scholarships are funding that does not come from own funding or parents, but is provided by the government, educational institutions, private companies, universities, and schools that can provide opportunities to increase human resource capacity through education. To increase student interest in learning in the school environment by providing scholarships or assistance to students who are economically disadvantaged. The process of selecting scholarship recipients includes three variables, namely report cards, attendance, and student attitudes. Based on the variables above, the data will be processed to produce student decisions that deserve scholarships with a success rate of 88.88%. In order to produce fast and precise decisions and to avoid mistakes in selecting students, we need an appropriate method that can be used to assist decision makers in carrying out their duties. By using the right method, the school will be easier to make decisions. The method to overcome this problem is through the application of fuzzy logic with the Sugeno method.